2017
DOI: 10.1002/2016jb013179
|View full text |Cite
|
Sign up to set email alerts
|

3‐D electrical resistivity structure based on geomagnetic transfer functions exploring the features of arc magmatism beneath Kyushu, Southwest Japan Arc

Abstract: Our 3‐D electrical resistivity model clearly detects particular subsurface features for magmatism associated with subduction of the Philippine Sea Plate (PSP) in three regions: a southern and a northern volcanic region, and a nonvolcanic region on the island of Kyushu. We apply 3‐D inversion analyses for geomagnetic transfer function data of a short‐period band, in combination with results of a previous 3‐D model that was determined by using Network‐Magnetotelluric response function data of a longer‐period ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Geotherms (gray lines) and average P‐T paths of the top of the slab in old/cold subduction zones and young/warm subduction zones are from Penniston‐Dorland et al (). Previous studies of lawsonite stability field suggest that lawsonite is stable on most P‐T path of old crusts (such as Japan; Hata et al, ), and breakdown occurs in young crusts such as Cascadia (McGary et al, ) at depths where conductive anomalies are observed (2.5–4 GPa).…”
Section: Discussionmentioning
confidence: 97%
“…Geotherms (gray lines) and average P‐T paths of the top of the slab in old/cold subduction zones and young/warm subduction zones are from Penniston‐Dorland et al (). Previous studies of lawsonite stability field suggest that lawsonite is stable on most P‐T path of old crusts (such as Japan; Hata et al, ), and breakdown occurs in young crusts such as Cascadia (McGary et al, ) at depths where conductive anomalies are observed (2.5–4 GPa).…”
Section: Discussionmentioning
confidence: 97%
“…The Kyushu-Palau Ridge was formed as part of the backarc system and features anomalously thick oceanic crust (Nishizawa et al, 2007). The projection of this ridge in the direction of plate convergence is roughly in the region of high mantle conductivity, as discussed in Hata et al (2017).…”
Section: Variability In the Presence Of A Deep Conductormentioning
confidence: 94%
“…Similarly, in the Kyushu subduction zone, which has featured 3D electromagnetic imaging using both network MT and geomagnetic transfer function approaches (Hata et al, 2015(Hata et al, , 2017, there is significant variability in the mantle wedge conductivity, with only one region, beneath Kirishima volcano, associated with a significant melt-related conductor (Fig. 7).…”
Section: Variability In the Presence Of A Deep Conductormentioning
confidence: 99%
“…Two additional features were identified from the electrical resistivity distribution beneath Aso caldera based on three-dimensional (3-D) resistivity models (Hata et al, 2016): a magma pathway imaged as a series of northward-dipping conductive anomalies from depths of~10 km to the Aso volcano edifice and earthquake clusters within resistive blocks rather than conductive blocks (i.e., the inferred magma pathway). In addition, previous 3-D resistivity models at coarser scales (>10 km), based on network-MT and geomagnetic depth sounding data, have suggested that the crust beneath the graben is a discontinuous high-conductivity belt, in which resistivity values are higher around Aso caldera than at comparable depths around other volcanoes (Handa, 2005;Hata et al, 2015Hata et al, , 2017. On the other hand, we need a 3-D resistivity model/distribution for the crustal structure beneath the whole of the graben at finer scale (<several kilometers) to further verify the relation between the resistivity distribution and the volcanic range and seismicity in and around the graben.…”
Section: Introductionmentioning
confidence: 98%